Private operators in the local markets of public services - Chądzyński, Jacek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The article presents selected results of research carried out as a part of the research project “Local authority between the state, society and the market: cooperation and competition”, which was conducted at the commission of the Ministry of Science and Higher Education and was financed with its means. The subject of the analysis are opinions of respondents (representatives of communes’ authorities and private entrepreneurs) concerning the participation of private operators in the local market of public services. Presented material allowed to formulate significant conclusions regarding the level of involvement of private operators in providing services that would meet the needs of a commune, its entities and inhabitants, relations that are present at this market and the main barriers of the involvement of private operators in this type of activity
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 476, s. 106-117
Keywords: commune; public services; private operators; cooperation and competition; gmina; usługi publiczne; podmioty prywatne; współpraca i konkurencja